Configurational analysis of cubebins and bicubebin from Aristolochia lagesiana and Aristolochia pubescens - de Pascoli, I. C.; Nascimento, I. R.; Lopes, LMX (Elsevier B.V., 2006)
(8S,8'R,9S)-, (8R,8'R,9R)-, and (8R,8',R,9S)-cubebins, together with (8R,8'R,8R,8'''R,9R,9S)-bicubebin, were isolated from Aristolochia lagesiana and Aristolochia pubescens. Their structures were determined by spectroscopic methods, including H-1 and C-13 NMR spectroscopy at low temperatures, and by chemical transformations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Aristolochia pubescens; Aristolochia lagesiana; Aristolochiaceae; lignan; cubebin; butyrolactol; bicubebin